2018
DOI: 10.18196/mb.9259
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Struktur Modal dan Profitabilitas terhadap Nilai Perusahaan dengan Kepemilikan Manajerial sebagai Variabel Moderasi

Abstract: Penelitian ini bertujuan untuk mengkaji pengaruh struktur permodalan dan profitabilitas perusahaan nilai dengan kepemilikan manajerial sebagai variabel moderasi. Populasi dalam penelitian ini adalah perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia (BEI) dalam periode 2013 hingga 2016. Data yang dikumpulkan oleh metode purposive sampling dan sampling hasil yang diperoleh adalah 96 sampel. Teknik analisis digunakan analisis regresi dikelola (MRA) atau interaksi tes. Hasilnya menunjukkan bahwa ibukota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
4
32

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 6 publications
6
16
4
32
Order By: Relevance
“…This result contradictory by research by Suryana and Rahayu (2018) and Kadafi (2020) who found that profitability had a negative effect on firm value. But this result in line with research conducted by Lubis et al (2017), Sukmawardini and Ardiansari (2018) and Kusumawati and Rosady (2018) who found that profitability has a positive effect on firm value. So, H4 is acceptable.…”
Section: The Effect Of Return On Equity On Pegsupporting
confidence: 91%
See 2 more Smart Citations
“…This result contradictory by research by Suryana and Rahayu (2018) and Kadafi (2020) who found that profitability had a negative effect on firm value. But this result in line with research conducted by Lubis et al (2017), Sukmawardini and Ardiansari (2018) and Kusumawati and Rosady (2018) who found that profitability has a positive effect on firm value. So, H4 is acceptable.…”
Section: The Effect Of Return On Equity On Pegsupporting
confidence: 91%
“…When the ROE owned by the company is not able to make a profit, even tends to lose money, the firm value will also decrease. This result contradicts the research Lubis et al (2017), Sukmawardini and Ardiansari (2018), Kusumawati and Rosady (2018) who found that profitability has a positive effect on firm value. However, these results are in line with research Suryana and Rahayu (2018) and Kadafi (2020) who found that profitability had a negative effect on firm value.…”
Section: The Effect Of Roe On Peg Through Percontrasting
confidence: 79%
See 1 more Smart Citation
“…The increase in return on assets will attract more investors. Return on the asset significantly affects the firm value [13], [25] [31] and [32].The proposed hypotheses in on the following:…”
Section: The Return On Assets and The Firm Valuementioning
confidence: 99%
“…The use of managerial ownership as a moderation variable also gives different results which managerial does not have any effect on the value of the company [24], while other study found managerial ownership affects the relationship between debt to equity ratio and firm value with the price to book value (PBV) [25]. Dewi and Tarnia (2011), in their study, used Tobin's Q as a measurement of firm value.…”
Section: Introductionmentioning
confidence: 98%